THE USE OF THE DEMPSTER SHAFER METHOD FOR DIAGNOSIS OF VULVOVAGINITIS - Sarah Indriani; Adi Prijuna Lubis; Rohminatin (Informatika, Universitas Jenderal Soedirman, 2022)
There are so many diseases caused by the female sex organs, one of which is vulvovaginitis. People's ignorance about the existence of Vulvovaginitis disease makes them not know the cause of this disease and how to prevent this disease and provide the right solution to deal with this disease. The purpose of this research is to build and design an expert system application to diagnose vulvovaginitis in women and to find out the right solution for vulvovaginitis in women based on the symptoms experienced by using the Dempster Shafer method. For calculations using the Dempster Shafer method, a measurement is carried out, each phenomenon is translated into several problem components, variables and indicators. Each determined variable is measured by providing numerical symbols, assigning a weight value (Belief, Plausibility) for each symptom in vulvovaginitis disease and mathematical calculation techniques can be carried out to diagnose vulvovaginitis disease for a symptom, so as to produce a generally accepted conclusion in a parameter. The result of this study is that the application of an expert system for diagnosing vulvovaginitis can identify the disease and symptoms of vulvovaginitis with the Dempster Shafer method by calculating the trust value of an expert on the symptoms entered. It is hoped that this research will help the public to find out Vulvovaginitis in women and provide the right solution to overcome it.